Peran Video Dakwah di Youtube dalam Meningkatkan Kesadaran Keagamaan pada Remaja di Era Digital - Anis Marti; Ahmad Khairul Nuzuli; Aan Firtanosa (Calathu: Jurnal Ilmu Komunikasi, 2023)
Dakwah content is material or content created and delivered with the aim of spreading the teachings of Islam and transforming the thoughts, attitudes, and actions of individuals or communities to be closer to Allah SWT. The method used in this research is qualitative descriptive with a phenomenological approach. The research findings indicate that dakwah content covering religious topics, social issues, and personal lives of teenagers has an appeal to them. Dakwah practitioners need to act as filters and ensure that the dakwah content delivered through digital media, including YouTube, has beneficial value and aligns with religious teachings. Digital media, especially YouTube, provides great opportunities to spread positive and valuable dakwah messages. Dakwah content has significant potential for growth through the use of digital media, particularly the YouTube platform. However, dakwah practitioners need to address challenges such as appropriate use of digital media, considering controversies in dakwah content, and understanding the interests and needs of their audience. In facing controversies surrounding dakwah content on the YouTube platform, the complex differences in perspectives should be acknowledged. Therefore, it is important to use appropriate language, select non-controversial dakwah materials, and maintain the accuracy and validity of the content delivered. These steps are taken to avoid unwanted controversies and prevent potential negative impacts. Keywords: dakwah content, digital media, YouTube, religious topics, controversy